2008
DOI: 10.1136/thx.2007.082974
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial response pattern of antigen presenting cells and regulatory T cells in children less than 2 years of age

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
4
33
0
Order By: Relevance
“…Studies of Tregs in bronchial asthma, as opposed to allergy are much more limited, but there is evidence to suggest that they are associated with the disease in both paediatric (89)(90)(91)(92) and adult (93)(94)(95)(96)(97) patients. Probably, the most convincing evidence for a role of Foxp3+ Treg in preventing the development of atopic disease stems from studies of the X-linked autoimmunity-allergic dysregulation syndrome, also termed immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome.…”
Section: Studies Of Treg In Human Bronchial Asthmamentioning
confidence: 99%
“…Studies of Tregs in bronchial asthma, as opposed to allergy are much more limited, but there is evidence to suggest that they are associated with the disease in both paediatric (89)(90)(91)(92) and adult (93)(94)(95)(96)(97) patients. Probably, the most convincing evidence for a role of Foxp3+ Treg in preventing the development of atopic disease stems from studies of the X-linked autoimmunity-allergic dysregulation syndrome, also termed immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome.…”
Section: Studies Of Treg In Human Bronchial Asthmamentioning
confidence: 99%
“…However, studies comparing transbronchial biopsies from young adult asthmatics and controls found no correlation between the presence BALT and a history of respiratory allergy or asthma (Sue-Chu et al, 1998). Similarly, the presence of BALT in infants does not correlate with lung function or atopy (Heier et al, 2008). However, the reactivity of BALT does increase in asthma patients (Elliot et al, 2004), with larger BALT areas found in subjects with asthma compared to either nonsmokers or smokers.…”
Section: Balt and Asthmamentioning
confidence: 94%
“…However, induction of mucosal immunity can take place also in nasopharynxassociated lymphoid tissue (NALT), including the unpaired nasopharyngeal tonsil (adenoids) and the paired palatine tonsils (see Chapter 103), as well as other lymphoepithelial structures of Waldeyer's pharyngeal ring (Brandtzaeg, 1987(Brandtzaeg, , 2011aBrandtzaeg and Johansen, 2005). BALT may also contribute, but this type of MALT is normally absent or rare in healthy lungs of adults although often present in children and adolescents-regularly being detected shortly after birth (Hiller et al, 1998;Heier et al, 2008Heier et al, , 2011.…”
Section: Malt Structuresmentioning
confidence: 98%
“…These organs make up most of Waldeyer's pharyngeal lymphoid ring and may play a major role in mucosal immunity in human airways, because BALT structures are not present or are quite rare in normal lungs of adults and are seen in only 40-50% of ordinary bronchial specimens from adolescents and children (Hiller et al, 1998), although they are regularly present at low frequency shortly after birth (Heier et al, 2008(Heier et al, , 2011. Also, human nasal mucosa contains only occasional ILFs and they are undetectable in mucosal specimens from at least 60% of children below 2 years of age (Debertin et al, 2003).…”
Section: Nasopharynx-and Bronchus-associated Lymphoid Tissuementioning
confidence: 99%